PENGGUNAAN INFORMASI SISTEM AKUNTANSI MANAJEMEN DALAM INTENSITAS PERSAINGAN PASAR UNTUK PENINGKATAN KINERJA PERUSAHAAN - WIDODO, HARIO (Berkala Ilmiah Mahasiswa Akuntansi)
The main purpose of this paper is to investigate the importance of accounting information systems in the intensity of the market that could affect the company's performance, and whether these effects can be mediated by the usefulness of broad scope and aggregation characteristics of management accounting information systems. Besides evaluating the importance of decision making and managerial activities that will ultimately improve managerial performance, job satisfaction and company performance. It can be concluded that the effect of the benefits of management accounting information to company performance and job satisfaction depends on the intensity of market competition. Under the high-level intensity of market competition, the benefits of advanced SAM information has a positive impact on company performance and job satisfaction, but under low levels of SAM have a negative impact information. Besides that the intensity of market competition is a determinant of information use and performance of the company's SAM. It means that organizations that use information SAM can effectively face competition in the market and thus improve performance.